Versatile Sequential Casting Processing for Highly Efficient and Stable Binary Organic Photovoltaics. Issue 33 (17th July 2022) - He, Chengliang; Pan, Youwen; Lu, Guanghao; Wu, Baohua; Xia, Xinxin; Ma, Chang‐Qi; Chen, Zeng; Zhu, Haiming; Lu, Xinhui; Ma, Wei; Zuo, Lijian; Chen, Hongzheng
Abstract: Forming an ideal bulk heterojunction (BHJ) morphology is a critical issue governing the photon to electron process in organic solar cells (OSCs). Complementary to the widely‐used blend casting (BC) method for BHJ construction, sequential casting (SC) can also enable similar or even better morphology and device performance for OSCs. Here, BC and SC methods on three representative donor:acceptor (D:A) blends are utilized, that is, PM6:PC71 BM, PM6:IT‐4F and PM6:L8‐BO. Higher power conversion efficiencies (PCEs) in all cases by taking advantage of beneficial morphology from SC processing are achieved, and a champion PCE of 18.86% (certified as 18.44%) based on the PM6:L8‐BO blend is reached, representing the record value among binary OSCs. The observations on phase separation and vertical distribution inspire the proposal of the swelling–intercalation phase‐separation model to interpret the morphology evolution during SC processing. Further, the vertical phase segregation is found to deliver an improvement of device performance via affecting the charge transport and collection processes, as evidenced by the D:A‐ratio‐dependent photovoltaic properties. Besides, OSCs based on SC processing show advantages on device photostability and upscale fabrication. This work demonstrates the versatility and efficacy of the SC method for BHJ‐based OSCs. Abstract : Sequential casting (SC) processing is practical and universal for device performance improvement in both fullerene‐ and nonfullerene‐based systems of organic solar cells (OSCs). A swelling–intercalation phase‐separation model is proposed to interpret the morphology evolution during SC processing. Notably, a champion efficiency of 18.86% (certified as 18.44%) is reached from SC processing, representing the highest value among binary OSCs.